Frail by Different Measures: A Comparison of 8-year Mortality in The Irish Longitudinal Study on Ageing (TILDA) - Romero-Ortuno, Roman; Kenny, Rose; O'Halloran, Aisling (My University, 2021)
Purpose: We compared the ability of four frailty identification tools (frailty phenotype: FP; FRAIL scale; 32-item Frailty Index: FI; and Clinical Frailty Scale: CFS) to predict 8-year mortality in TILDA. Methods: We included wave 1 (2010) participants with data for all four tools. Mortality was ascertained at wave 5 (2018). Age, sex and education-adjusted binary logistic regression models were computed. Results: At baseline, there were 5700 participants (mean age 63, range 50–98, 54% women). Frailty prevalences were 2.3% by FRAIL, 3.8% by FP, 10.9% by CFS, and 12.8% by FI. Mortality was 41.2%, 44.9%, 25.3% and 27.0%, respectively. The highest adjusted OR for mortality was for FRAIL (OR 4.48, 95% CI 2.93–6.85, P < 0.001), followed by FP (OR 3.55, 95% CI 2.52–5.00, P < 0.001), FI (OR 2.10, 95% CI 1.68–2.62, P < 0.001), and CFS (OR 1.88, 95% CI 1.48–2.38, P < 0.001). Conclusions: All tools significantly predicted mortality, but FRAIL and FP seemed more specific.
PUBLISHED
Keywords: Frailty; Mortality; Comparative study; Longitudinal study; Older people; Ageing; Age-related disability; Chronic Health Condition; Mental Health/Psychosocial disability; Mobility impairment; Third age/ageing